2019
DOI: 10.1111/psyp.13431
|View full text |Cite
|
Sign up to set email alerts
|

Monetary feedback modulates performance and electrophysiological indices of belief updating in reward learning

Abstract: Belief updating entails the incorporation of new information about the environment into internal models of the world. Bayesian inference is the statistically optimal strategy for performing belief updating in the presence of uncertainty. An important open question is whether the use of cognitive strategies that implement Bayesian inference is dependent upon motivational state and, if so, how this is reflected in electrophysiological signatures of belief updating in the brain. Here, we recorded the EEG of parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
0
4
2
Order By: Relevance
“…We examined the context of varying reward stakes on information sampling and found that while individuals maintained the same underlying strategy between both contexts, reward increased the overall information that people gathered. Our results differ from that observed in a reinforcement learning task, where reward stakes resulted in a switch to a more intensive but optimal strategy (Bennett et al, 2019). Additional investigation is needed into how individuals use context to evaluate when to switch information sampling strategies and when to adapt an existing strategy.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We examined the context of varying reward stakes on information sampling and found that while individuals maintained the same underlying strategy between both contexts, reward increased the overall information that people gathered. Our results differ from that observed in a reinforcement learning task, where reward stakes resulted in a switch to a more intensive but optimal strategy (Bennett et al, 2019). Additional investigation is needed into how individuals use context to evaluate when to switch information sampling strategies and when to adapt an existing strategy.…”
Section: Discussioncontrasting
confidence: 99%
“…Behaviorally, participants in the high-reward condition over-sampled, effectively raising the stopping threshold without changing the underlying computations; both drawing more samples and waiting until they achieved a larger difference between categories. This stands in contrast with prior work that suggested increasing monetary stakes can increase one’s motivational state, thereby encouraging the use of more optimal but expensive strategies (Bennett et al, 2019; Manohar et al, 2015). Why might increased monetary stakes encourage behavioral adjustments but not push participants towards optimal behavior?…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…In recent years, some studies have investigated habituation to stimuli using P300 [24][25][26][27], but the effects of predictability (uncertainties and prediction errors) on brain activity related to novelty habituation remain unclear. Kopp (2007) was the first to study the relationship between Bayesian inference and P300 components [28], and several empirical studies have also now been conducted [29][30][31][32][33]. Kolossa et al showed the correspondence between surprise as the amount of information and P300 [32].…”
Section: Introductionmentioning
confidence: 99%